2010
DOI: 10.1124/jpet.110.174839
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Prednisolone Treatments Increase Bioactive Vitamin B6Synthesis In Vivo

Abstract: The etiology of vitamin B 6 depletion in inflammation remains unknown. Hepatic vitamin B 6 decreased in adrenalectomized rats, and such reductions were restored by an acute muscle injection of a very high dose of glucocorticoids. We tested the hypothesis that long-term prednisolone treatment for treating inflammation restores vitamin B 6 status by induction of tissue B6 metabolic enzymes. Two independent in vivo models were used. Lewis rats and C57BL/6J mice received prednisolone regimens that reflected clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Interestingly, Lacour et al (4) previously suggested that the deficit in plasma PLP in RTRs could originate from the period on dialysis and that it might be maintained by the immunosuppressive medication used by RTRs; however, they acknowledge that data for such a drug-induced effect were lacking (5). To our knowledge, the potential in vivo effects of prednisolone on vitamin B-6 isoforms have been investigated in one intervention study in experimental animals (28). It was found that long-term prednisolone treatment increased circulating plasma concentrations of PLP, pyridoxal, and pyridoxic acid in rats and mice.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Lacour et al (4) previously suggested that the deficit in plasma PLP in RTRs could originate from the period on dialysis and that it might be maintained by the immunosuppressive medication used by RTRs; however, they acknowledge that data for such a drug-induced effect were lacking (5). To our knowledge, the potential in vivo effects of prednisolone on vitamin B-6 isoforms have been investigated in one intervention study in experimental animals (28). It was found that long-term prednisolone treatment increased circulating plasma concentrations of PLP, pyridoxal, and pyridoxic acid in rats and mice.…”
Section: Discussionmentioning
confidence: 99%
“…Before the dietary intervention, mice were fed the AIN‐93M diet (2 mg folic acid/kg, Dyets, Bethlehem, PA) for 2 weeks for adaptation and then were fed either the folate‐supplemented diet (20 mg folic acid/kg), or the folate‐deficient diet (0 mg folic acid/kg) that were based on the AIN‐93M formula except for the folate content. Vitamin‐free casein was used in both diets . Mice were fed the designated diets for an additional 8 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Vitamin-free casein was used in both diets. 29 Mice were fed the designated diets for an additional 8 weeks. Mice fed the chow diet (2 mg folic acid/kg) ad libitum throughout the study were used as a reference group for adequate folate status.…”
Section: Conditions and Dietsmentioning
confidence: 99%
“…Briefly, perchloric acid-extracted tissue supernatant fluid was incubated (30 min in the dark) with derivatization solution (250 mg semicarbazide and glycine/mL). Samples were filtered through 0.45-mm microspin filters before HPLC analysis (28). The HPLC system consisted of a Hitachi L-2130 intelligent pump connected to an L-2480 fluorescence detector and L-2100 autosampler (Hitachi).…”
Section: Determination Of Vitamin B-6 and Homocysteine Concentrationsmentioning
confidence: 99%
“…Study 2 investigated the effects of longterm physiologic doses of celecoxib and naproxen treatments on vitamin B-6 metabolism in hypercholesterolemic animals. In study 1, 18 male, 4-wk-old C57BL/6J mice (National Laboratory Animal Center) were fed a standard AIN-93M diet (Dyets) that contained 6 mg pyridoxine/kg diet throughout the study period (28). In study 2, 18 male, 7-wk-old Syrian hamsters (National Laboratory Animal Centern) were fed a modified AIN-93M hypercholesterolemic diet (10% corn oil plus 0.2% cholesterol) that contained 6 mg pyridoxine/kg diet throughout the study period (Dyets).…”
Section: Animals Diet and Study Conditionsmentioning
confidence: 99%